Migration constraints and disparate responses to changing job opportunities - Kalee E. Burns; Julie L. Hotchkiss (Federal Reserve Bank of Atlanta, 2019)
Using the Current Population Survey between 1996 and 2018, this paper investigates the role constraints to migration might play in explaining racial/ethnic disparities in the labor market. The Delta Index of dissimilarity is used to illustrate a greater distributional mismatch between race/education specific workers and jobs among minorities relative to white non-Hispanics. Regression analysis then shows that this mismatch is consistent with minorities being less responsive to changes in the distribution of job opportunities. However, minorities are more responsive when the growing job opportunities are located in areas with greater same-racial/ethnic representation, suggesting that social constraints might play a role in the observed distributional mismatch. The analysis focuses on 25-54 year old men.
Keywords: J61; J15; J18; 330; racial labor market disparities; migration costs; Delta Index; social costs; place-based; people-based; mismatch